2011
DOI: 10.1007/s11661-011-0836-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Prediction of Hot Deformation Flow Curves

Abstract: The modeling of hot flow stress and prediction of flow curves for unseen deformation conditions are important in metal-forming processes because any feasible mathematical simulation needs accurate flow description. In the current work, in an attempt to summarize, generalize, and introduce efficient methods, the dynamic recrystallization (DRX) flow curves of a 17-4 PH martensitic precipitation hardening stainless steel, a medium carbon microalloyed steel, and a 304 H austenitic stainless steel were modeled and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 89 publications
0
39
0
Order By: Relevance
“…As a result, considerable research has been carried out to model the flow stress of metals and alloys. [4][5][6][7][8][9] A constitutive relationship is a mathematical representation of flow stress as a function of temperature, strain rate, strain, and occasionally other factors such as chemical composition. [9,10] Usually, the effect of temperature and strain rate is incorporated in the ZenerHollomon parameter (Z), which is a temperaturecompensated strain rate parameter.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, considerable research has been carried out to model the flow stress of metals and alloys. [4][5][6][7][8][9] A constitutive relationship is a mathematical representation of flow stress as a function of temperature, strain rate, strain, and occasionally other factors such as chemical composition. [9,10] Usually, the effect of temperature and strain rate is incorporated in the ZenerHollomon parameter (Z), which is a temperaturecompensated strain rate parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the effects of work hardening and softening mechanisms are considered during the plastic deformation, and it is necessary to remove the elastic stage of the flow curves [29]. Figure 2 shows the θ-ε and θ-σ curves of the Fe-6.5wt.…”
Section: Flow Behavior Characteristicsmentioning
confidence: 99%
“…The positive values of θ indicate that the work hardening exceeds the dynamic softening. The peak stress and corresponding strain can be obtained from the flow curve, whereas the true peak stress (σ ) and strain (ε ) can be calculated from the θ-ε and θ-σ curves when θ = 0 [29], as presented in Table 2. It can be observed that the work hardening rate increased with the decrease of temperature and increase of strain rate, as shown in Figure 2a.…”
Section: Flow Behavior Characteristicsmentioning
confidence: 99%
“…The modeling of hot flow stress and the prediction of flow curves are important in metal-forming processes from the mechanical and metallurgical standpoints because this is an essential part of the numerical simulations in finite element codes. As a result, considerable researches have been focused on this subject in recent years [6,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%